2018
DOI: 10.1016/j.neuroimage.2017.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent compared to continuous real-time fMRI neurofeedback boosts control over amygdala activation

Abstract: Real-time fMRI neurofeedback is a feasible tool to learn the volitional regulation of brain activity. So far, most studies provide continuous feedback information that is presented upon every volume acquisition. Although this maximizes the temporal resolution of feedback information, it may be accompanied by some disadvantages. Participants can be distracted from the regulation task due to (1) the intrinsic delay of the hemodynamic response and associated feedback and (2) limited cognitive resources available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 59 publications
2
45
1
Order By: Relevance
“…Therefore, the two elements, frequency of feedback presentation and NFT type, were intertwined and could not be separated. A previous study comparing continuous vs intermittent feedback using percent signal change in the amygdala in healthy young adults showed that participants were able to learn to increase the target NFT levels using both approaches, although intermittent feedback was more effective than continuous in that study (Hellrung et al, 2018). In our study we did not find any evidence for a difference between the two approaches.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Therefore, the two elements, frequency of feedback presentation and NFT type, were intertwined and could not be separated. A previous study comparing continuous vs intermittent feedback using percent signal change in the amygdala in healthy young adults showed that participants were able to learn to increase the target NFT levels using both approaches, although intermittent feedback was more effective than continuous in that study (Hellrung et al, 2018). In our study we did not find any evidence for a difference between the two approaches.…”
Section: Discussioncontrasting
confidence: 82%
“…Although targeting SMA-striatal connectivity is theoretically motivated by knowledge regarding the disease mechanism and was identified as a potential target in our previous study (Papoutsi et al, 2018), we did not find any reliable evidence that it was better or worse than activity NFT. Both activity (Young et al, 2017;Hellrung et al, 2018) and connectivity (Megumi et al, 2015;Ramot et al, 2017;Yamashita et al, 2017) NFT have been used successfully in other studies, suggesting that both methods are effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is perfectly justified in regard to the fact that neuronal network rhythmic activity at specific frequency bands is thought to contribute to information transfer and processing in the brain (Engel, Fries, & Singer, 2001;Fries, 2005). In fMRI-guided NF protocols, the target function is often the BOLD signal amplitude in well-defined brain regions (Caria & de Falco, 2015;Hellrung et al, 2018;Young et al, 2014;Zotev, Misaki, Phillips, Wong, & Bodurka, 2018;Zotev et al, 2011). However, a target could in principle be any function of possibly spatially (Koush et al, 2015;Ruiz, Buyukturkoglu, Rana, Birbaumer, & Sitaram, 2014) and temporally (Diaz Hernandez, Rieger, Baenninger, Brandeis, & Koenig, 2016;Ros et al, 2017) non-local dynamics.…”
Section: Acting On Brain Dynamics: What Where Howmentioning
confidence: 99%
“…As a consequence, future studies investigating neurofeedback applications within the DMN or trying to regulate input-sensitive regions should consider to use intermittent neurofeedback. In two recent studies, it has been found that intermittent neurofeedback was even more efficient for participants in the regulation process than continuous neurofeedback information (Hellrung et al, 2018;Johnson et al, 2012). Advantages of intermittent feedback are that it is robust against noise present in the data, and participants do not have to get used to the inherent delay of the BOLD signal.…”
Section: Reversal and Training Effects In The Dmn Up-regulation Sessionmentioning
confidence: 99%